Contralesional cross-over in chronic neglect: Visual search patterns reveal neglect of the ipsilesional hemispace. - Gall, Carolin; Günther, Tobias; Fuhrmans, Franziska; Sabel, Bernhard A. (NeuroRehabilitation, 2012)
Introduction: With neuropsychological rehabilitation approaches neglect patients can learn to compensate for the reduced awareness of the contralesional hemispace that is often observed after right brain damage. Here, we report contralesional "cross-over" deviations in line bisection that are hypothesized to be a result of focusing on the contralesional hemispace while the intact hemispace is "neglected". We investigate whether this unexpected pattern of deviation is related to defects in the visual field, motor intention/hypokinesia deficits or deficits in working memory. Methods: Neglect patients with and without homonymous field defects were screened for contralesional cross-over deviations in line bisection of long lines. During line bisection eye movements were recorded in two conditions with and without requiring hand movements in order to search for directional hypokinesia. Visual fields were tested with near-threshold perimetry and with supra-threshold campimetry. Results: Of 53 chronic neglect patients only 8 showed cross-over in line bisection. Evidence for directional hypokinesia was found in only one patient. Patients with cross-over focused more often to the left than to the right of the objective line midpoint. Patients with and without visual field defects did not differ in the extent of cross-over deviations. Cross-over deviation and inconsistent stimulus detection in left hemispace were correlated irrespective of the presence of a visual field deficit. Larger cross-over deviations were associated with poorer verbal working memory span, and disorganized patterns of eye movement were related to reduced visuo-spatial working memory capacity. Conclusion: Increasing awareness of the disorder and the use of compensatory strategies may have led to a cross-over shift of visual search dominance towards the neglected side resulting in an exploration deficit of the ipsilesional side.